Students’ learning approaches as a factor of academic achievement at selected public universities: A cross-sectional study - Negash, Tadese Tamire; Eshete, Million Tesfaye; Hanago, Getu Ataro (Frontiers in Education, 2022)
Introduction: Excellence in anesthesia education has been advocated to meet the current and future needs of the society. Universities play a key roles in creating a conducive climate for learning and facilitating the developments of expected competencies among the graduates. This study assessed students’ learning approaches and the relationship with their academic achievement at two selected public universities of Ethiopia. Methods: A cross-sectional study was conducted on 123 anesthesia students. All 3rd and 4th year anesthesia students were recruited for the study.. Study Skills Inventory for Students (ASSIST) were used to assess students’ learning approaches. Perceived performance, Cumulative Grade Point Average (cGPA) and 100 MCQ items were used to assess the academic achievement. Data were entered into Epi-data and exported to SPSS for statistical analysis. An independent t-test was used to determine the presence of difference in academic achievement across learning approaches. Bivariate and multivariable linear regressions were fitted to assess the association of students’ characteristics and learning approaches with their academic achievement. A P-value of less than 0.05 was used to declare the statistical significance. Result: There were no statistically significant differences between the groups on the most of the learning approaches and academic achievement measures. On multivariable linear regression, entrance exam result, students’ perception of the definition of learning and deep approach to learning were found to be predictors of students’ academic achievement (ß = 0.004 & P =0.03, ß = 0.14 & P= 0.015 and ß = 0.13 & P = 0.023) respectively. Conclusions: In this study, students mainly follow deep approaches to learning and there were no statistically significant differences between the groups on most of the learning approach measures and academic achievements. Entrance exam result, positive perception on the definition of learning and deep approach to learning were found to be positive predictors for academic achievement. Emphasis has to be given to improving students’ learning approaches for better academic achievement and success. Keywords: academic achievement, higher education, learning approaches, students’ performance, university students